Collapse of farmland bird populations in an Eastern European country following its EU accession. Issue 1 (27th June 2018) - Reif, Jiří; Vermouzek, Zdeněk
Abstract: Eastern European countries are considered a stronghold for the continent's farmland biodiversity. The abundance of farmland birds is one important element of this biodiversity. At the end of the 20th century, member states of the European Union (EU) experienced serious population declines of farmland birds due to agricultural intensification, which was not observed in the Eastern European nonmember states. In 2004, 10 mostly Eastern European countries acceded to the EU. It is thus important to ask whether this historical step resulted in changes of agricultural production and, in turn, in farmland bird populations. Here we used annual crop yields and monitoring data on farmland bird abundance in an Eastern European new EU‐member state and showed that agricultural production intensified and farmland bird populations declined steeply after country's EU accession. These results indicate that entering EU's Common Agricultural Policy caused significant deterioration of farmland biodiversity in a once biodiversity‐rich region.